Correlated multistate model for the progression of chronic kidney disease with detecting risk factors effect. - Taha, Ahsan Abdalkhaliq; Mohammad, Monem Aziz (Revista Latinoamericana de Hipertensión, 2023)
AIM: This study examined a multistate model with correlated frailty between CKD transitions by fitting a model with a bivariate gamma distribution. Methodology: By incorporating as a frailty term, correlated multistate modeling was able to account for the dependence between moderate and severe CKD in an analysis of kidney dysfunction progression data from 153 patients. Therefore, frailty and correlated-frailty multistate models were used to evaluate the role that significant prognostic factors play in disease progression. Results: Hypertension and diabetes have a threefold and fourfold increased risk of progressing from state mild to moderate CKD in both models respectively, covid-19 has a significant risk of transitioning from mild to moderate and severe CKD state in both models. Conclusion: The underlying dynamics of CKD can be better understood with the help of multistate models, which do this by analyzing the subjects' entire event histories. Under the hypothesis of a positive correlation between the frailties for the two exits from mild CKD, this evidence supports the superiority of a model fit with a bivariate gamma distribution.